IMPLEMENTASI MODEL PEMBELAJARAN BERPUSAT PADA SISWA DALAM PENGEMBANGAN KOMPETENSI GLOBAL: STUDI KASUS DI SMA MODERN AL RIFAIE 2 MALANG - Hesim Muzedi; Zulfan Zahansyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to analyze the construction and implementation of learning models in improving students' global competencies at SMA Modern Al Rifaie 2 Malang, as well as to examine the supporting and inhibiting factors in their implementation and their implications for students' global competencies. This study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students as the primary data sources. Data analysis was conducted using Miles and Huberman’s interactive model through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the learning models implemented at SMA Modern Al Rifaie 2 Malang are oriented toward student-centered learning, collaborative learning, and contextual learning approaches. The implementation of these learning models is carried out through discussions, presentations, group work, project-based learning, and problem-solving activities that encourage active student engagement. These learning models enhance students’ global competencies by strengthening intercultural communication skills, critical thinking, collaboration, and openness toward cultural diversity and global perspectives. Supporting factors include a conducive modern Islamic boarding school environment, teacher competence, school support, a collaborative culture, and the habituation of foreign language use. Meanwhile, inhibiting factors include differences in students’ language abilities, limited technological facilities, and varying levels of students’ self-confidence. Furthermore, students’ global competencies are developed through the integration of Islamic values such as tasamuh (tolerance), ta'awun (mutual assistance), and ukhuwwah (brotherhood), resulting in students who possess both religious character and global perspectives. ABSTRAK Penelitian ini bertujuan untuk menganalisis konstruksi dan implementasi model pembelajaran dalam meningkatkan kompetensi global siswa di SMA Modern Al Rifaie 2 Malang, serta mengkaji faktor pendukung dan penghambat dalam penerapannya beserta implikasinya terhadap kompetensi global siswa. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi dengan melibatkan kepala sekolah, guru, dan siswa sebagai sumber data utama. Analisis data menggunakan model interaktif Miles dan Huberman melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa model pembelajaran yang diterapkan di SMA Modern Al Rifaie 2 Malang mengarah pada pendekatan student-centered learning, collaborative learning, dan pembelajaran kontekstual. Implementasi model pembelajaran dilakukan melalui diskusi, presentasi, kerja kelompok, pembelajaran berbasis proyek, dan pemecahan masalah yang mendorong keterlibatan aktif siswa. Model pembelajaran tersebut mampu meningkatkan kompetensi global siswa melalui penguatan kemampuan komunikasi lintas budaya, berpikir kritis, kerja sama, serta keterbukaan terhadap keberagaman budaya dan perspektif global. Faktor pendukung implementasi meliputi lingkungan pesantren modern yang kondusif, kompetensi guru, dukungan sekolah, budaya kolaboratif, dan pembiasaan penggunaan bahasa asing. Adapun faktor penghambat meliputi perbedaan kemampuan bahasa siswa, keterbatasan fasilitas teknologi, serta tingkat kepercayaan diri siswa yang beragam. Selain itu, kompetensi global siswa juga dikembangkan melalui integrasi nilai-nilai Islam seperti tasamuh, ta'awun, dan ukhuwwah sehingga terbentuk karakter siswa yang religius sekaligus berwawasan global.